Determinants of the Stock Return – Exchange Rate Dynamic Linkage in India and China - Mohan, Abha; Mathew, Tomy; Daniel, Roy Sam (Indian Journal of Finance, 2025)
Purpose : The present study tried to identify the macroeconomic variables that determined the dynamic linkage between stock return and exchange rate in two prominent emerging economies: India and China. The determinants of the stock return–exchange rate linkage varied from country to country depending on the various economic policies of a particular economy. Methodology : Dynamic conditional correlation (DCC) values representing the stock return–exchange rate linkage were derived by performing the DCC-GARCH model. Furthermore, the potential macroeconomic factors such as capital flows, trade balances, interest rate, money supply, output, inflation, oil price, and world stock market were regressed on the estimated DCC series to find the significant determinants. Findings : A significant spillover between the stock returns and exchange rates was found in India and China. Further, we found capital flow, money supply, and oil price to be the significant determinants of India’s stock return–exchange rate linkage. However, in China, the interest rate was the only significant determinant. Practical Implications : The study was helpful for policy-makers in framing effective policies to stabilize and integrate the financial markets and for investors in framing diversification and hedging strategies while investing in emerging markets. Originality/Value : Numerous researchers empirically studied the linkage between stock returns and exchange rates and examined the determinants of stock return movements and exchange rate fluctuations separately. However, the significant determinants of the stock return–exchange rate linkage were not investigated adequately, especially in emerging economies.